Kesiapan Guru PAI dalam Mengimplementasikan Kurikulum 2013 di SMA Sidoarjo dan SMK Antartika Sidoarjo - Karimullah Karimullah; Upik Khoirul Abidin (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2021)
This article is intended to capture the extent to which PAI teachers are prepared to implement the 2013 Curriculum at the SMA and SMK levels in Sidoarjo. Readiness is seen from the planning, process, and assessment. This research is a qualitative research with interview data collection technique, observation and documentation study. The main data sources in this study were PAI teachers at SMAN 3 and SMK Antarctica 1 Sidoarjo. The results showed that in general the readiness of PAI teachers in implementing the 2013 curriculum at SMAN 3 Sidoarjo and SMK Antarctica 1 Sidoarjo was good, starting from aspects of planning, implementation and assessment of learning. However, a number of obstacles were found, namely in the aspect of learning planning including the lack of understanding of PAI teachers about the 2013 curriculum; in the aspects of the implementation of learning including not being able to apply the scientific approach to the maximum; on aspects of learning assessment including the number of instruments and assessment formats that must be prepared.